2021
DOI: 10.18678/dtfd.994776
|View full text |Cite
|
Sign up to set email alerts
|

D-Galaktoz ile İndüklenen Farelerde Yaşlanma Modelinin Nefropatisi Üzerine Mirisitrin ve Vitamin E’nin Koruyucu Etkileri

Abstract: Aim: Aging occurs in cells and tissues due to oxidative stress in physiological conditions. D-galactose (DG) is widely used to cause aging in animal studies. In this study, the renal protective effects of myricitrin and vitamin E in the aging mice model induced by DG was evaluated. Material and Methods: Subcutaneous DG injection was used for induction of the aging model. 72 female mice were randomly divided into six groups: All groups were received DG at 500 mg/kg/d for six weeks. In the last 28 days, the grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…D-Gal causes aging progression and nephropathy in the brain, kidney, and liver. It also induces oxidative stress by increasing lipid peroxidation [41]. In the present study, the effects of TQ on the changes caused by AlCl3+D-Gal in the testicular tissue of rats, which were administried to create an experimental Alzheimer's model, were investigated.…”
Section: Discussionmentioning
confidence: 96%
“…D-Gal causes aging progression and nephropathy in the brain, kidney, and liver. It also induces oxidative stress by increasing lipid peroxidation [41]. In the present study, the effects of TQ on the changes caused by AlCl3+D-Gal in the testicular tissue of rats, which were administried to create an experimental Alzheimer's model, were investigated.…”
Section: Discussionmentioning
confidence: 96%
“…Imenshahidi et al demonstrated that crocins, safranal (12), and the extract of C. sativus can reduce the mean arterial pressure in both healthy and hypertensive rats depending on the dose [43].…”
Section: Antihypertensionmentioning
confidence: 99%
“…Crocins are utilized extensively as colorants and flavoring agents in the food, cosmetics, and pharmaceutical industries [ 5 ]. They exhibit a broad spectrum of pharmacological activity, including antitumor [ 6 ], anti-inflammatory [ 7 ], hepatoprotective [ 8 ], nephroprotective [ 9 ], antidepressant [ 10 ], antioxidant [ 11 ], and antidiabetic [ 12 ] properties. The Saffron Multi-glycoside Tablet (Xihonghua Zonggan Pian) ameliorates myocardial ischemia or myocardial infarction induced by coronary ligation.…”
Section: Introductionmentioning
confidence: 99%